TAWASSUT ATTITUDE RELEVANCE NAHDLATUL ULAMA IN PREVENTING EXTREMISM - Siswoyo Aris Munandar; Ummu Azizatul Kubro (Jurnal Studi Agama dan Masyarakat, 2021)
What was currently happened is the legitimacy of violence, which justified theologically as the term jihad fī sabīlillāh. Radicalisms believed and felt they had the right to commit acts of violence in the name of religion and God. In facts, what they were doing was violating religious rules and staying away from God. The attitude of tasawuf and tawassut in Nahdlatul Ulama prevented radicalism. Based on the background of the problems described above, the study focused on how was the concept of tawassut and tasawwuf in preventing radicalism movements? The purpose was to find out the meaning of tawassuf in Nahdlatul Ulama and to describe the concept of tawassut and tasawwuf  in preventing radicalism. The results revealed that tawassuṭ and tasawuf which were a meeting point between the two, discuss how to realize the attitude of tawassut in Nahdlatul Ulama in the digital era, and discuss the actualization of the attitude of tawassuṭ in realizing peace.